Service Quality in The Public Service: A Combination of SERVQUAL and Importance-Performance Analysis - Andina Liestyanti; Widhyawan Prawiraatmadja (AIBPM Publisher, 2021)
This study aims to measure the quality of service obtained at The Provincial Office of the Indonesian FDA in Jakarta (BBPOM in Jakarta) through a survey with Front-Liner Employees (FLE) and customer perceptions of service quality. The study examines how closely customer service expectations match Front-Liner Employees' perceptions use SERVQUAL. The survey elicits customers' expectations of excellent public service and compares them to their perceptions of BBPOM in Jakarta. Additionally, the paper discusses a parallel SERVQUAL survey conducted on Front-Liner Employees, how effectively they understand their consumers' needs and how well their internal processes support the delivery of excellent public services. The findings reveal that there is a gap exists in meeting customer expectations. Importance-Performance Analysis (IPA) is a tool to decide the priority scale for each existing attribute's improvement efforts and the priority scale for current improvements. Based on the IPA of the discrepancy between customer expectations and employees' perceptions, attributes of tangibles dimension (T1, T2, and T3) are essential flaws that require immediate improvement. While the gap between customer expectations and their perception of the service obtained in IPA, attributes T1, RP4 and A1 need immediate improvement.